Female labour market participation in Europe: Novel evidence on trends and shaping factors - Angela Cipollone; Eleonora Patacchini; Giovanna Vallanti (IZA Journal of European Labor Studies, 2014)
We investigate the changes in women's participation patterns across 15 EU countries over the last 20 years using individual data from ECHP and EUSILC databases. Our findings show that the observed trends in female participation differ substantially both across countries and across different groups of women. We explore such heterogeneity in trends by looking at the effects of policies and labour market institutional factors on the participation of women with different family and individual characteristics. Our estimates reveal a role of policies and institutions that is stronger than what has so far been assessed. Labour market institutions and family-oriented policies explain almost 25% of the actual increase in labour force participation for young women, and more than 30% for highly educated women. Surprisingly, changes in the institutional and policy settings contribute less in explaining the participation of low-skilled women. We also find that reforming the institutional framework towards a model of "flexicure" labour market is effective in enhancing women labour supply only when deregulation is accompanied by sufficient social compensation.
Keywords: J11; J21; J2; 330; Employment gender gap; Labor market institutions; Child-rearing; Elderly care; Flexicurity